Assessment of an objective structured clinical examination (OSCE) for undergraduate students in accident and emergency medicine. Issue 4 (December 1994) - Johnson, G; Reynard, K
Abstract : Conventional techniques for assessing the knowledge and clinical competence of undergraduate medical students are widely acknowledged as being unsatisfactory. We introduced an objective structured clinical examination (OSCE) for our fourth year medical students at the end of their accident and emergency (A&E) medicine attachment. This paper outlines the organisation of the examination and the results of a comparison of marks obtained from the OSCE, from a multiple choice type examination and from a subjective rating of the students performance by their teachers. We found the OSCE to be an acceptable form of examination to both medical students and examiners. Our results show significant correlation between marks obtained on the OSCE exam and subjective rating of the students ability. There was no statistically significant relationship to marks obtained on a multiple choice questionnaire exam. The OSCE format is particularly appropriate to A&E medicine where the participation of patients in traditional clinical examinations is impractical.